Land reform with human capital: A new analysis using the theory of economic growth and the theory of the firm - Sousa, Miguel Rocha de (2013)
In section 1 we refer to a historical synopsis, section 2 classifies the different land reforms using KAWAGOE (1999) typology. Afterwards we link the concepts of human capital and land reform within the theory of economic growth. In section 3 a simplified formal dynamic model of land reform based on the neoclassical theory of economic growth is introduced, following SOLOW-SWAN models. In section 4 an endogenous growth model tries to evaluate land reform in the process of economic growth, based on the ROMER (1990) model. We further try to relate the notion of convergence with successful land reform. The main conclusion of these sections is that with the neoclassical exogenous framework there is convergence between small landholders and latifundia holders. This is a successful land reform: there is a finite time horizon that allows almost landless illiterate to catch up with rich literate farmers. In the case of endogenous growth there is never convergence thus the land reform process fails. Another conclusion in the endogenous framework is that, by reverse causality, failed land reforms result from perpetuating initial differential human capital stocks. In section 5, another approach is to extend ARROW (1962) learn by doing model to evaluate land reform as a structural break (or cut-off point). A condition for land reform viability is established, creating a Possibility Set of Recovery of Human Capital (PSRHC). In section 6 we simplify the theory of the firm JOVANOVIC´s (1982) model, applying it to agricultural firms to explain birth, life and death of latifundia. We establish the date and process of land reform, as a cut-off process, in which it arises from the failure of firms. Finally, in section 7, we conclude and present in section 8 the references.